Productivity gains of DevOps adoption in an IT team: a case study - Silva, M. A. (2018)
The main purpose of this research is to determine the productivity gains from the merge of two traditional IT teams: Development and Operations into a single DevOps team implementing 6 DevOps capabilities. On this research the authors go through the existing DevOps literature to better frame this research and the reader. To answer the formulated research questions the authors analyzed the team capacity divided by tasks before and after a DevOps transition and interviewed 5 senior team members to collect their opinion about this transition. The main object objective is to analyze if there were productivity gains of that team after making the transition to a DevOps approach.